Tissue inhibitor of metalloproteinases (TIMP)-1 creates a premetastatic niche in the liver through SDF-1/CXCR4-dependent neutrophil recruitment in mice - Seubert, Bastian; Sleeman, Jonathan P. (Hepatology, 2014)
Due to its ability to inhibit prometastatic matrix metalloproteinases, tissue inhibitor of metalloproteinases (TIMP)-1 has been thought to suppress tumor metastasis. However, elevated systemic levels of TIMP-1 correlate with poor prognosis in cancer patients, suggesting a metastasis-stimulating role of TIMP-1. In colorectal cancer patients, tumor as well as plasma TIMP-1 levels were correlated with synchronous liver metastasis or distant metastasis-associated disease relapse. In mice, high systemic TIMP-1 levels increased the liver susceptibility towards metastasis by triggering the formation of a premetastatic niche. This promoted hepatic metastasis independent of origin or intrinsic metastatic potential of tumor cells. High systemic TIMP-1 led to increased hepatic SDF-1 levels, which in turn promoted recruitment of neutrophils to the liver. Both inhibition of SDF-1-mediated neutrophil recruitment and systemic depletion of neutrophils reduced TIMP-1-induced increased liver susceptibility towards metastasis. This indicates a crucial functional role of neutrophils in the TIMP-1-induced premetastatic niche. Conclusion: Our results identify TIMP-1 as an essential promoter of hepatic premetastatic niche formation.
Gesehen am 16.08.2017